A Review On Case Studies Of Office Building Facades In Malaysia Based On Maqasid Syariah - Shaza Liyana Shamri; Elina Mohd Husini; Azhani Abd Manaf; Nurul Hadirah Muszaffarsham; Mohd Zin Kandar (Universiti Sains Islam Malaysia, 2024)
Date: 9 September 2021 Platform: MSTeams, USIM Nilai, Negeri Sembilan, Malaysia.